Unveiling the interplay of Continuing Professional Development Strategies and Teacher Success in the Iranian EFL Context - Mahnaz Saeidi; Abdolraoof samii; Masoud Zoghi (Journal of Applied Linguistics)
<span style="color: #1f1f1f; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">The global education landscape is witnessing a rise in teacher accountability, where educators bear a heightened responsibility for demonstrably achieving student learning outcomes. In response, teachers are engaged in a continuous quest to enhance their pedagogical effectiveness, seeking strategies and methodologies to optimize their classroom practice. The present study investigates the relationship between Continuous Professional Development (CPD) practices and teacher success in the Iranian context. A sample of 364 EFL teachers from junior and senior high schools self-reported on their CPD engagement, while 422 of their students provided their perceptions of teacher success. Findings revealed the substantial potential of CPD to elevate teacher success through interconnected processes of knowledge updating, reflective practice, collaborative learning, and refined decision-making skills. Notably, updating knowledge strongly influenced both collaboration and reflection, while reflection moderately stimulated collaboration, and collaboration exerted a robust influence on effective decision-making. However, the study unexpectedly uncovered a negative direct association between teacher decision-making and professional success within the specific Iranian context. Additionally, no significant gender-based differences in teacher success were observed. The negative association between teacher decision-making and professional success in the Iranian context warrants further investigation. This suggests that factors specific to the Iranian educational system or cultural context might influence the relationship between these two variables. Understanding these factors is crucial for developing contextually relevant CPD programs.